The Special Collection Fond of the Presidents of Ukraine as an Integrated Informational Resource for Research on the Institution of the Presidency. (2nd April 2016) - Udovyk, Volodymyr
ABSTRACT: The article describes the functions of the special collection Fond of the Presidents of Ukraine (FPU) within the V. I. Vernadsky National Library of Ukraine, as well as the history of its formation, purpose, activities, and operational features. It emphasizes that the main characteristics of the institution are not only collecting and using various types of documents, but also research and informational-analytical work to popularize them among citizens and authorities. Unlike the US presidential libraries, in Ukraine the conception of the FPU envisages it as an integrated documentary and informational-analytical center to collect heritage materials and study the institution of the presidency as a whole. FPU also provides operative scholarly and informational resources to government officials, to the scholarly community, to the broad student community, and to society in general through the Internet portal of the V. I. Vernadsky National Library of Ukraine and social networks.